2019
DOI: 10.1136/bmjopen-2018-023563
|View full text |Cite
|
Sign up to set email alerts
|

Association between alcohol and drug use and arrest for driving under the influence after crash involvement in a rural area of Norway: a case–control study

Abstract: ObjectivesThe rate of deaths caused by road traffic crashes is particularly high in rural areas. It has been hypothesised that one factor that may contribute is differences in patterns of alcohol use. The aim was to compare the prevalence of psychoactive substances among crash-involved drivers arrested for suspicion of driving under the influence (DUI) who are tested for alcohol and drugs and recent random drivers in a rural area. Furthermore, we investigated the association between traffic crashes and driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…This outcome is in keeping with previous research that found a similar higher prevalence of DUIA among males and younger adults in the USA 42 46 47 and Norway. 48 In Jamaica, the legal age limit for purchasing alcohol and acquiring a driver's license is 18 years. 20 49 These legal coincidences likely explain this observation among younger drivers, as research has shown an association between securing a driver's license and increased substance use.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is in keeping with previous research that found a similar higher prevalence of DUIA among males and younger adults in the USA 42 46 47 and Norway. 48 In Jamaica, the legal age limit for purchasing alcohol and acquiring a driver's license is 18 years. 20 49 These legal coincidences likely explain this observation among younger drivers, as research has shown an association between securing a driver's license and increased substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is estimated that around 5 % -7 % of fatal crashes were attributed to drink driving [22]. There are numerous published results of studies on the influence of antidepressants, opiates, alcohol, psychoactive substances and various diseases on the number and outcome of traffic accidents [16,17,23,19]. Benzodiazepines are considered "light psychoactive drugs" which do not produce much effect.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on driving under the influence (DUI) of psychoactive substances (alcohol, psychoactive medicinal drugs, and illicit drugs) has mainly revolved around topics such as the prevalence of DUI and the risks associated with road traffic injuries and deaths. [1][2][3][4][5] DUI poses a threat to the lives and safety of people who engage in DUI, 6 as well as other road users 7 ; however, the research regarding future outcomes of people convicted of DUI of alcohol and drugs is both limited and somewhat outdated. 8 9 Drivers who engage in DUI have been characterised by serious health problems such as substance use and dependence, major depressive disorders, anxiety disorders, hyperactivity disorders and risk-taking dispositions.…”
Section: Introductionmentioning
confidence: 99%